Model Checking Software 23rd International Symposium, SPIN 2016, Co-located with ETAPS 2016, Eindhoven, The Netherlands, April 7-8, 2016, Proceedings - Bošnački, Dragan; Wijs, Anton (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 23rd International Symposium on Model Checking Software, SPIN 2016, held in Eindhoven, The Netherlands, in April 2016. The 16 papers presented, consisting of 11 regular papers, 1 idea paper, and 4 tool demonstrations, were carefully reviewed and selected from 27 submissions. Topics covered include model checking techniques, model checking tools, concurrent system semantics, equivalence checking, temporal logics, probabilistic systems, schedule and strategy synthesis using model checking, and verification case studies.